Constructing fatherhood in the North and South: paid parental leave, work and care in Iceland and Spain - Arnalds, Asdis, A.; Belope Nguema, Sabina; Eydal, Guðný Björk; Fernández Cornejo, José Andrés (Acta Sociologica, 2022)
While Iceland and Spain historically belong to two different welfare regimes, both countries have enacted fathers’ quotas to their systems of paid parental leave. From the year 2000, Iceland has provided fathers with a three-month-long quota, and Spain introduced a 13-day fathers’ quota in 2007. Using survey data, the article applies structural equation modelling to learn of the interconnection between parents’ leave use, their working hours and fathers’ participation in care of their children. Fathers’ leave use was found to be associated with their involvement in care in both countries, both directly and indirectly, through the reduction in working hours. Icelandic fathers were more engaged in childcare than fathers in Spain, which could be explained by the longer period of paid leave available for fathers in Iceland. FEM2014-56723-P Depto. de Economía Aplicada, Pública y Política Fac. de Ciencias Económicas y Empresariales TRUE pub